2021
DOI: 10.1108/stics-10-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Hong Kong’s response to COVID-19: a glance to the control measures and their enforcement

Abstract: Purpose This study aims to examine Hong Kong’s responses to COVID-19, arguing that Hong Kong’s relatively low infection rate is due to self-discipline of citizens together with the enforcement measures introduced by the government. Design/methodology/approach This study reviewed the government policy announcements and the prevailing scholarly analyses on Hong Kong society during COVID-19. Findings It starts by examining the partial lockdown and control measures since mid-January, and the roles of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Participants reported heavy involvement in infection-prevention behaviors during CNY (mean = 4.16) and became even more involved during summer 2020. This finding might be related to increases in COVID cases between CNY 2020 and summer 2020 ( 6 ), along with stringent public health policy (e.g., restrictions on gatherings) concerning prevention behaviors ( 18 , 19 ). Furthermore, this result is aligned with findings from the end of the SARS pandemic ( 52 ): More than 70% of the participants reported that they would wear a mask in public places and avoid going to crowded places if new SARS cases ever were to surface in HK again.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants reported heavy involvement in infection-prevention behaviors during CNY (mean = 4.16) and became even more involved during summer 2020. This finding might be related to increases in COVID cases between CNY 2020 and summer 2020 ( 6 ), along with stringent public health policy (e.g., restrictions on gatherings) concerning prevention behaviors ( 18 , 19 ). Furthermore, this result is aligned with findings from the end of the SARS pandemic ( 52 ): More than 70% of the participants reported that they would wear a mask in public places and avoid going to crowded places if new SARS cases ever were to surface in HK again.…”
Section: Discussionmentioning
confidence: 99%
“…However, participants didn't take more action to remain healthy during summer 2020 as anticipated, possibly because HK residents might have encountered barriers to increasing healthy behaviors (e.g., exercising and dieting) during the COVID-19 pandemic. For example, fitness centers were closed from mid-March 2020 to early September 2020 ( 19 ), and the living spaces in residential buildings are limited, leading to difficulties in exercising at home ( 53 ). As a result, the participants did not significantly adopt more actions to stay healthy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Making use of legal regimes, Hong Kong still imposes effective supervision and intervention in the performance of these quasi-public/private service providers by means of budget control and auditing requirements. COVID-19 has underlined a great number of involvements from "non-public personnel, but they are actually the contractors of the government" (Hsieh et al, 2021;Ho and Chan, 2021). This anti-pandemic model marks a sharp departure from the general emphasis of centrally administered, mass mobilisation of practices in most non-democratic Asian regimes.…”
Section: Reflectionsmentioning
confidence: 99%